2017
DOI: 10.22159/ajpcr.2017.v10i3.16311
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induction Effect of Curcumin and Its Analogs Pentagamavunon-0 and Pentagamavunon-1 on Cancer Cell Lines

Abstract: Objectives: This experiment aims to investigate the apoptosis effect of curcumin and its analogs pentagamavunon-0 (PGV-0) and PGV-1 on normal and other cancer cell lines.Methods: Growth inhibition effect was investigated using the MTT method. Double staining used acridine orange, 2-(4-aminodiphenyl)-6-indolcarbamidine dihydrochloride and ethidium bromide was performed to determine morphological changes of cells. Detection of PARP, caspase-3, PUMA and BAX using a western blot method was conducted to elucidate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…1 Previously, we reported a new curcumin analogue, namely PGV-1 (Figure 1) to have potential anti-cancer activities against several cancer cells. 2,3 Our studies showed that curcumin and pentagamavunon-1 (PGV-1) inhibit the activity of nuclear factor kappa B (NFκB) in vitro and interact with the HER2 receptor in silico . 4 Furthermore, we also found that PGV-1 increases the cytotoxicity of 5-fluorouracil (5-FU) in WiDR colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…1 Previously, we reported a new curcumin analogue, namely PGV-1 (Figure 1) to have potential anti-cancer activities against several cancer cells. 2,3 Our studies showed that curcumin and pentagamavunon-1 (PGV-1) inhibit the activity of nuclear factor kappa B (NFκB) in vitro and interact with the HER2 receptor in silico . 4 Furthermore, we also found that PGV-1 increases the cytotoxicity of 5-fluorouracil (5-FU) in WiDR colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin has been well known to have anticancer activity (Meiyanto 1999). It is proven to inhibit the growth of cancer cells by inducing apoptosis (Da'i et al 2017) and increasing ROS levels beyond the threshold (Larasati et al 2018). Therefore, PGV0 may inhibit the growth of cancer cells in the same pathway as curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…1a and b, 2d and e). On various cancer cell lines that might prompt apoptosis through translocation of Bax that activate caspase to induce apoptosis [32].…”
Section: Ramadoss and Sivalingammentioning
confidence: 99%